2021
DOI: 10.14507/epaa.29.5687
|View full text |Cite
|
Sign up to set email alerts
|

A política de contratação de professores temporários na rede municipal de ensino de Cametá (Pará, Brasil, 2013-2020)

Abstract: This paper aims to analyze the temporary teachers’ hiring policy in Cametá, during the last two municipal administrations (2013–2020). The main focus is the interface between disputes for local power and the municipal administration of education. This is a case study using a qualitative approach, employing the procedures of documental analysis, interviews, participant observation, and a survey for data collection. Our theoretical framework was based on understandings from the anthropology of politics, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
(30 reference statements)
0
4
0
2
Order By: Relevance
“…Venco (2018), analisando os efeitos do paradigma da Nova Gestão Pública em municípios paulistas, evidencia as relações entre baixas condições de trabalho, contratos flexíveis dos professores temporários e estudantes de perfil mais vulnerável. Ampla literatura indica que os professores temporários trabalham em condições precárias, pois não têm seus vencimentos vinculados a um Plano de Cargo, Carreira e Remuneração (PCCR) (FERREIRA, 2013), são constrangidos a regularmente trocar de escola (MARQUES, 2006) e, no limite, não são protegidos pela legislação trabalhista (FERREIRA, 2013;COSTA, 2021). Além das condições piores em relação aos professores efetivos, Silva Jr. e Oliveira (2019) destacam, a partir do caso baiano, as desvantagens dos professores temporários em relação, inclusive, às regras da CLT, evidenciando que esse tipo de contrato que cria regimes especiais que não reproduzem elementos básicos de proteção ao trabalhador.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Venco (2018), analisando os efeitos do paradigma da Nova Gestão Pública em municípios paulistas, evidencia as relações entre baixas condições de trabalho, contratos flexíveis dos professores temporários e estudantes de perfil mais vulnerável. Ampla literatura indica que os professores temporários trabalham em condições precárias, pois não têm seus vencimentos vinculados a um Plano de Cargo, Carreira e Remuneração (PCCR) (FERREIRA, 2013), são constrangidos a regularmente trocar de escola (MARQUES, 2006) e, no limite, não são protegidos pela legislação trabalhista (FERREIRA, 2013;COSTA, 2021). Além das condições piores em relação aos professores efetivos, Silva Jr. e Oliveira (2019) destacam, a partir do caso baiano, as desvantagens dos professores temporários em relação, inclusive, às regras da CLT, evidenciando que esse tipo de contrato que cria regimes especiais que não reproduzem elementos básicos de proteção ao trabalhador.…”
Section: Introductionunclassified
“…Para responder as questões definiram-se cinco variáveis de análise, verificando se elas impactam nos municípios paraenses em relação ao percentual de professores temporários em suas redes de ensino, considerando os fatores causais apontados pela literatura, já previamente explicitados (SANTOS, 2016;ALVES;2020;COSTA, 2021). Mais especificamente as três últimas variáveis de análise tiveram como inspiração a mencionada literatura.…”
Section: Introductionunclassified
“…Venco (2018) analyzed the effects of the New Public Management paradigm in São Paulo municipalities, highlighting the relationships between low working conditions, flexible contracts of temporary teachers, and students with more vulnerable profiles. Numerous studies have indicated that temporary teachers work under precarious conditions since their salaries are not linked to a Plan of Position, Career, and Remuneration (FERREIRA, 2013); they are regularly forced to change schools (MARQUES, 2006), and at the limit, they are not protected by labor legislation (FERREIRA, 2013;COSTA, 2021). In addition to worse conditions than permanent teachers, Silva Jr. and Oliveira (2019) highlighted, based on the case of Bahia State, the disadvantages of temporary teachers in relation, even to CLT rules, revealing that this type of contract creates special regimes that do not reproduce basic elements of worker protection.…”
Section: Introductionmentioning
confidence: 99%
“…The authors analyzed the case of Minas Gerais and highlighted the multiple ruptures of bonds that the bureaucracy involved in temporary contracts subjects teachers to. Feldman and Alves (2020) and Feldman and Costa (2021), in turn, conducted case studies, respectively, in the Pará municipalities of Portel and Cametá, investigating the policy of hiring temporary teachers in these two municipal networks; both studies indicated that teaching work is an important part of these municipalities' formal salaried labor market. In Portel, between 2011 and 2017, teachers in the municipal network represented an average of 37% of the salaried workers registered by the Annual Social Information Report (RAIS); in Cametá, between 2011 and 2018, they represented an average of 24%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation